Male song variation of Green Violetear (Colibri thalassinus) in the Talamanca Mountain Range, Costa Rica - Barrantes Montero, Gilbert (2008)
We studied variation in acoustic and temporal characteristics of the static male song of the Green Violetear (Colibri thalassinus) in a single population in Costa Rica. The static song of 19 males was extremely variable. The song has two elements: the first was delivered exclusively at the beginning of each song while the second was present once, twice, or three times in the song of different males. Low frequency (LF), song duration (ΔT), and high frequency (HF) varied significantly among most individuals. The male population of Green Violetear has four song types that differ in acoustic and temporal characteristics. The great inter-male song variation suggests this type of vocalization may be under sexual selection.